Online Participation and Information Inclusion – A Study of Internet Users with Vision Impairments - Chandrashekar, Sambhavi; Caidi, Nadia (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l’ACSI, 2013)
Our presentation will highlight the need to move beyond Web Accessibility for Internet users with vision impairments to Information Inclusion through facilitation of their online participation and knowledge sharing. Our empirically grounded suggestions emanate from our study of the everyday information practices of sixty residents of Ontario with vision impairments. Cette communication met en évidence la nécessité d'aller au-delà de l'accessibilité sur le web pour les internautes souffrant de troubles de la vision pour privilégier plutôt l'inclusion par l'information au moyen d'une meilleure participation en ligne et du partage des connaissances. Nos suggestions se basent sur des données empiriques provenant de l'analyse des pratiques quotidiennes de soixante résidents ontariens souffrant de troubles de la vision.